Fixed Point Theorems for Almost Z-Contractions With An Application - Isik, H.; Gungor N.B.; Park C.; Jang S.Y. (MDPI AG, 2018)
In this paper, we investigate the existence and uniqueness of a fixed point of almost contractions via simulation functions in metric spaces. Moreover, some examples and an application to integral equations are given to support availability of the obtained results. © 2018 by the authors.
Keywords: Almost contraction; Complete metric space; Fixed point; Simulation function